Leachability Of Arsenic From Wastes Of Arsenic Removal Units Using Modified Toxicity Characteristic Leaching Procedure (Journal of Life and Earth Science, 2012)
The present study evaluated the leaching of arsenic from sludge/waste of seven SONO filters that were operated in Rajarampur of Chapai Nawabganj district. For this, Toxicity Characteristic Leaching Procedure (TCLP) test was performed. To understand actual leaching of arsenic, a Simulated Natural Column (SNC) that is comparable to natural mature landfill was devised. Total arsenic concentration (AsT) was measured by HG-AAS. The studied arsenic waste/sludge, having 7.0-9.2% solid content, were alkaline in nature (pH values of 7.9-8.7) and had arsenic and iron concentrations of 4.54-5.50 and 480-1039 mg kg-1 respectively. The TCLP test reveals that 6.4-19.4% (average 14%) of arsenic was leached from the waste (average leachate AsT before and after TCLP were 5.04 and 0.71 mg kg-1 respectively). After 102 days of continuous operation in SNC, AsT in the leachate was found to be 0.223 mg L-1, although initial AsT was 0.350 mg L-1. It was observed that AsT in SNC leachate increased up to 54 days (corresponding to 1.741 mg L-1) and then decreased in reciprocal quadratic pattern. Comparison shows that TCLP underpredicts 14.2% of arsenic leaching than that of SNC. Since leachate AsT in both methods did not exceed the USEPA regulated level of 5 mg L-1, the studied waste/sludge was not hazardous. DOI: http://dx.doi.org/10.3329/jles.v6i0.9716 JLES 2011 6: 19-26